Magneto-rheological abrasive finishing (MAF) of soft material using abrasives. (2021) - Rampal, Rohit; Goyal, Tarun; Goyal, Deepam; Mittal, Manoj; Kumar Dang, Rajeev; Bahl, Shashi
Abstract: Magnetorheological finishing is highly developed unconventional machining process used for nanometer range surface finishing with the help of magnetic abrasive particles. The cutting forces are generated and controlled by the magnetic field in this process, which is developed between the electromagnetic poles and magnetic abrasives. Excellent process capabilities were attained by this technology. But one of the major limitation or drawbacks is in the wide utilization of the process in industries. This is due to the huge cost of magnetic abrasives, which act as cutting tool in these processes. Very few studies have been performed in the direction of development of new or alternative magnetic abrasives. The present research mainly focuses on the development of magnetic abrasives and performance of these magnetic abrasives. This investigation aims to develop magnetic abrasives by different techniques i.e. Simple Mixing, Adhesive bonding, Microwave sintering and Mechanical alloying, then investigating the performance on brass work piece with SiC abrasives and to find the best technique. The surface topography was done through the x-ray diffraction (XRD) and scanning electron microscope (SEM) to analyze the surface obtained after finishing. The Mechanical Alloying is the best technique concluded through this work to prepare the magnetic abrasives, which further gives the best results in terms of Material removal rate (MRR) and percentage improvement in surface finish (PISF) upon the internal surface of hollow cylindrical brass pipes.